Process geomorphology - Ritter, Dale F. (Waveland Press, 2011)
The twenty-first century offers distinct challenges to the geosciences. Today's geomorphologist must interact with and decipher problems that face hydrologists, engineers, geologists, pedologists, foresters, and many others. The bond that unites geomorphology with so many diverse disciplines is the common need to understand the processes of surface mechanics, which is exceedingly important as we struggle to comprehend the impacts of climate changes, tectonic events, and their effects on our physical environment.\While maintaining the introductory yet applied focus of previous editions, the authors have mined the most current research and data for the fifth edition. A wealth of new photos and figures augment and add depth to each field, providing an expansive base for students to build upon. A detailed bibliography enhances the further study of any topic of interest.